Theoretical assumptions for saving energy of electrical heating water in the solar collector – battery - Kunelbayev, Murat; Merembayev, Timur; Yunussov, Rassul; Aizhan, Irzhanova; Yedilchan, Didar (The 6th International Conference on Nanomaterials and Advanced Energy Storage Systems. Institute of Batteries LLP, Nazarbayev University, and PI “National Laboratory Astana”., 2018)
In this article a theoretical assumptions in the energy saving energy source of the solar collector – accumulator is presented. One of the main features of the solar collector - accumulator is the electric hot water in a cold season, or in night days of a sun radiation. The experiments showed that conventional thermoelectric welding device, which is based on conventional power factor could be used to control a temperature of the nozzle from the initial temperature...
Keywords: energy; electrical heating water